(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Over the past few decades, the field of work in healthcare management and administration has changed dramatically. Hospitals have become large and very complex organizational systems. This led to the need for a thorough reorganization of the system of training managers in health care. Health systems in transition, as currently exist in the Republic of Croatia, are not flexible enough to accept scientific and practical insights into the role, content and meaning of management. The aim of this research is to gain an understanding of how directors in health care institutions perceive and understand management as a concept of health care management. The discriminant analysis method was used. The survey was conducted during 2019 on a quota sample of 26 directors and assistant directors in private and public health institutions in central Croatia. Despite the fact that this was a relatively small sample, the results of this analysis have yielded quite interesting results that may be useful in implementing the concept of management in healthcare institutions. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.